1992
DOI: 10.1002/jcb.240480109
|View full text |Cite
|
Sign up to set email alerts
|

Acute and chronic signals controlling glucose transport in skeletal muscle

Abstract: Glucose transport into muscle cells occurs through facilitated diffusion mediated primarily by the GLUT1 and GLUT4 glucose transporters. These transporter proteins are controlled by acute and chronic exposure to insulin, glucose, muscle contraction, and hypoxia. We propose that acute responses occur through recruitment of pre-formed glucose transporters from an intracellular storage site to the plasma membrane. In contrast, chronic control is achieved by changes in transporter biosynthesis and protein stabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
42
0
2

Year Published

1992
1992
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(45 citation statements)
references
References 59 publications
1
42
0
2
Order By: Relevance
“…Extrapancreatic effects of sulfonylureas in vitro and in vivo. In addition to adipose tissue, prolonged expo sure to high glucose has been reported to acutely and chronically downregulate the glucose transport system in skeletal muscle, which represents the major site for insulin-dependent glucose disposal (66). It will be inter esting to see in future studies whether glimepiride will compensate the lower number of GLUT4 in PM of muscle cells in the basal and insulin-stimulated state.…”
Section: Discussionmentioning
confidence: 93%
“…Extrapancreatic effects of sulfonylureas in vitro and in vivo. In addition to adipose tissue, prolonged expo sure to high glucose has been reported to acutely and chronically downregulate the glucose transport system in skeletal muscle, which represents the major site for insulin-dependent glucose disposal (66). It will be inter esting to see in future studies whether glimepiride will compensate the lower number of GLUT4 in PM of muscle cells in the basal and insulin-stimulated state.…”
Section: Discussionmentioning
confidence: 93%
“…The data further suggest that activation of p38 MAPK may participate in the stimulation of glucose uptake by both stimuli in rat skeletal muscle. Diabetes 49:1794-1800, 2000 T ranslocation of glucose transporters in muscle and fat cells is a prerequisite for full stimulation of glucose uptake by insulin (1,2). Activation of several lipid and serine/threonine kinases in an orderly fashion is believed to be required for this translocation.…”
mentioning
confidence: 99%
“…Prior studies in this cell type have demonstrated that insulin-stimulated glucose transport is mediated by the GLUT4 transporter (23,24,26), as is the case for skeletal muscle (27)(28)(29)(30). In this study, we used L6 GLUT4 cells that had been engineered to overexpress GLUT4 (23).…”
Section: Discussionmentioning
confidence: 99%